High Myopia and Strabismus Induced by a Deep Intronic Mutation in COL2A1. (3rd July 2021) - Rossenwasser-Weiss, Shirel; Orenstein, Naama; Zahavi, Alon; Goldenberg-Cohen, Nitza
ABSTRACT: Purpose : To characterize a genetic mutation causing Stickler syndrome in a previously undiagnosed family. Methods : Five generations of a single family suspected of having Stickler syndrome were evaluated clinically and genetically. Results : The demographic and clinical data yielded specific clinical phenotypes of Stickler syndrome in 13 family members; 7 had more than one clinical feature. Four family members underwent genetic analysis: the proband (index patient) and his mother, maternal grandfather, and healthy father. No relevant mutation was detected in the proband on whole exome analysis, but subsequent extension of the analysis to intronic areas yielded a deep intronic mutation, NM_001844.5:c.1527 + 135 G > A. Sanger sequencing was used to validate the results in the family members. Conclusions : Stickler syndrome has several subtypes with variable clinical features. Therefore, predicting the genetic locus of the disease based on clinical characteristics is challenging. We present a rarely described intronic mutation in COL2A1 . Genetic testing may aid in the early diagnosis of Stickler syndrome, which is important for genetic counselling, proper clinical management, and improved prognosis.